Risk Factors Leading to ST Elevation Myocardial Infarction in Young Patients Presenting to a Tertiary Care Hospital, Islamabad Pakistan - Muhammad Said Nawaz, Kalsoom Bibi, Syed Nasir Ali Shah, Nouman Khan, Muhammad Ilyas, Zarak Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the risk factors leading to ST Elevation Myocardial infarction in young patients presenting to a tertiary care hospital,Islamabad Pakistan Methodology: Prospective observational study was conducted at Pakistan Institute of Medical Sciences, Cardiology department, Islamabad, Pakistan for duration of 10 months. Study was conducted on sample size of 164 selected through non-probability consecutive sampling technique. Study included participants with age less than or equals to 45 and participants from both genders.However, participants with Age more than 45and those having non ST myocardial infarction were excluded. findings including Blood pressure, pulse, respiratory rate, cyanosis, S3, Killip class and JVP were noted. Data was entered and analyzed using statistical package for social sciences (SPSS). P value of < 0.05 was considered as significant. Results: Mean age of participant was found to be 25.3±4.3, mean BMI was found to be 25.8 ±0.81. Mean HB level was found to be 12.8±0.8 and mean respiratory rate was found to be 18. Risk factor HTN in association with gender was found to have significant difference between two with p value of 0.01 In study analysis it was seen that risk factor HTN in association with age was found to have significant difference between two with p value of 0.05.Smoking in association with age was found to have shown significant difference between two with p value of 0.02Family history of MI in association with age was found to have shown significant difference between two with p value of 0.04. Conclusion: Risk factors HTN ,Smoking and family history were found to be positively associated with ST elevation myocardial infarctionin young age.